IMPLEMENTING LEARNING MODEL BASED ON INTERACTIVE LEARNING COMMUNITY FOR EFL STUDENTS OF MUHAMMADIYAH UNIVERSITY - Eny Syatriana; Geminastiti Sakkir (Universitas Negeri Makassar, 2020)
The main objective of this study was to investigate speaking ability of Muhammadiyah University students. It is the most intense language ability which is used in communicating with others. Speaking material plays an important role in various language productions. Such conversation can be in the form of discussion, speech, debate, dialogue, storytelling, retelling. The speakers use oral language to express their desires, feelings, thoughts with others, so that people can understand what they want, but there are still many misunderstandings that can affect the students’ mastery of accuracy, fluency, flexibility and comprehensibility. A total number of 35 students in third semester studens have been involved in this study, who are sampled by using total sampling technique. From this study, it was found that leaning community can motivate students to speak up effectivelly. The students’ competence in speaking skills of Unismuh Makassar are not fully in line with curriculum expectations in terms of the critical thinking. Therefore, to achieve the goal of teaching speaking skills, lecturer are required to use the methods that can encourage the leaners’ interest and motivate more until their speaking skills can be improved. The key words of the learning community method are learning and sharing experiences with others, working with others to create better learning among members of groups enhance the awareness, confidance, and sharing experience. The finding of this study can improve the speaking abiity from learning community stages futhermore it has been answer the researh question in terms of the application of Learning Community can attract studets participation in oral skill.